Integrasi Kelembagaan dalam Perspektif Filsafat Ilmu: Sebuah Telaah Epistemologis dan Ontologis - A Wathon; Akhyak Akhyak; Ngainun Naim (Lembaga Yasin AlSys, 2025)
This study examines institutional integration from the perspective of the philosophy of science, an approach that has rarely been explored in depth, even though integration efforts to date have largely focused on managerial and structural aspects. In this context, a philosophical understanding of the epistemological, ontological, and axiological foundations underlying integration processes becomes crucial for achieving institutional sustainability and excellence. The study aims to analyze how principles of the philosophy of science can shape more coherent and effective institutional integration strategies, particularly in the domains of education and innovative governance. This research adopts a philosophical literature study and conceptual analysis approach to explore how epistemological convergence, ontological alignment, and axiological cohesion can serve as key pillars in building holistically integrated institutions. The findings indicate that institutional integration grounded in a robust philosophical understanding can generate deeper synergy, overcome knowledge fragmentation, and strengthen institutional identity. These results contribute significantly to the development of institutional integration theory by offering a more comprehensive framework, while also providing practical implications for leaders and policymakers in designing adaptive and future-oriented integration strategies. The study further opens avenues for continued exploration of institutional integration models informed by the philosophy of science framework across various types of organizations.